Price, Performance, and Government Policy Affecting Purchase Intention for Plug-in Hybrid Electric Vehicles in Nanning, China - Baoyao Huang; Lalita Puangmaha (Journal of Frontier in Economic and Management Research, 2026)
The research objectives were to study price, performance, and government policy in relation to consumers’ purchase intentions regarding plug-in hybrid electric vehicles (PHEVs) in Nanning, and to analyze the effects of price, performance, and government policy on consumers’ purchase intentions regarding plug-in hybrid electric vehicles (PHEVs) in Nanning. Conducted through a quantitative methodology involving a questionnaire survey of 400 residents in Nanning aged 18–60 who had not yet purchased PHEVs, the research utilized descriptive statistics, correlation analysis, and multiple regression analysis to test the hypotheses. The findings reveal that price, performance, and government policy are significantly related to consumers’ purchase intentions (p < .001). Furthermore, the multiple regression analysis indicates that these variables have significant positive effects on purchase intentions, explaining 51.1% of the variance in the model (R² = 0.511). The analysis demonstrates that government policy exerts the strongest influence on purchase intention (β = 0.371), followed by price (β = 0.277) and performance (β = 0.160). These results highlight that consumers in Nanning prioritize government policy and economic feasibility when considering PHEVs, providing empirical evidence that policy support is the paramount driver for promoting consumers purchase PHEVs in Nanning.